Evaluation of a novel algorithm for automating virtual surgical planning in mandibular reconstruction using fibula flaps. Issue 9 (September 2019) - Modabber, Ali; Rauen, Alexandra; Ayoub, Nassim; Möhlhenrich, Stephan Christian; Peters, Florian; Kniha, Kristian; Hölzle, Frank; Raith, Stefan
Abstract: Virtual surgical planning plays an increasingly important role in jaw reconstruction. The aim of the present study was the evaluation of the clinical applicability of a novel algorithm for automating virtual mandibular reconstruction using fibula flaps. The software uses Computed-Tomography of the facial skeleton and the lower leg of 63 subjects, implemented in Python programming language. The developed algorithm is based on individual bone curvatures of the mandible and fibula. Ten different defects were generated for each mandible by virtually defined cutting planes. Three experienced surgeons reviewed all reconstruction proposals generated by the algorithm according to a visual analogue scale. The possible correlation between the ratings and the prioritization of the algorithm and the calculation time for the reconstructions were analyzed. Spearman analysis showed a strong correlation −0.613 (p < 0.001) between the deviation of the reconstruction result from the target line and the average assessment of the surgeons as well as a moderate correlation −0.448 (p = 0.013) between surgeons' assessments and the prioritization by the algorithm. The calculation time for twenty reconstructions per defect took between 4.99 s and 483.5 s depending on defect size and location. The evaluated algorithm automatically creates valid reconstruction results with acceptable computation time, which have received a high level of confirmation from experienced surgeons.